Pediatric kidney transplantation: Long-term outcome of living versus deceased donor program from a single center- A retrospective observational study - Kinnari B Vala; Himanshu V Patel; Vivek B Kute; Divyesh P Engineer; Pankaj R Shah; Dinesh N Gera; Pranjal R Modi; Jamal S Rizvi; Bina Butala; Shruti Mehta; Vineet M Mishra (Indian Journal of Transplantation, 2020)
Background: Kidney transplantation (KT) is widely accepted as most successful treatment option for patients with end-stage kidney disease (ESKD) for better survival and quality of life for both children as well as adults. Data scarcity on long term outcome of living donor (LD) versus deceased donor (DD) pediatric KT in developing countries prompted us to review our experience. Aims and Objectives: To determine(1) long term graft, (2)patient survival outcome and (3) rejection episodes in LD versus DD pediatric KT in developing country. Patients and Methods: This was a retrospective observational analysis of 151 LD and 37 DD pediatric renal transplants (age ≤18 years) performed at a tertiary care center between 1998 and 2011. This study was under taken to evaluate long term patient and graft survival, rejection episodes and other complications. Demographic details for all patients was retrieved. Kaplan-Meier curves were used for survival analysis. Results: Over a mean follow-up of 4.2 ± 3.61 years, one-, five- and ten- year death-censored graft survival in LDKT was 87.4%, 72.1%, 72.1% and patient survival was 92.5%, 80.9%, 75.1% respectively; 19.8% (n = 30) patients had biopsy proven acute rejection (BPAR) and 17.8% (n = 27) patients died, mainly due to infections (n = 12). In DDKT, over mean follow-up of 3.93 ± 3.5 years, one-, five- and ten-year death-censored graft survival was 90.4%, 86.4% ,73.3% and patient survival was 83.4%, 67.9%, 67.9 %, respectively; 21.6% (n = 8) patients had BPAR and 27% (n =10) patients died, mainly owing to infections (n = 6). Conclusion: LDKT or DDKT in children has acceptable graft function with patient/graft survival over long-term follow-up, encouraging to develop sustained deceased donor program in developing countries. However, infections are major cause of morbidity and mortality.